Multi-array sensorised pillowcase as call detection alarm system for in ward tetraplegic patient / Normazlianita Mohamad Alias - Normazlianita, Mohamad Alias (2021)
Call bell systems play an important role for patients and nurse interaction in hospitals and at homes. Conventionally, when in danger or in need, a patient would press a call bell button for assistance. However, a large percentage of hospitalized patients are unable to use such device due to hand weakness or the device is unreachable to the patient when positioned away, especially for patients with tetraplegia. This problem has motivated the development of a fabric-based multi-array pressure sensor as a call bell garment that works by detecting the pressure pattern on a pillow surface where the patient is lying down. In this study, we utilized off-the-shelf materials to form: i) a fabric-based multiarray pressure sensor system, ii) an acquisition circuit along with interface and signal processing algorithms to acquire and interpret the sensor data. To ensure the functionality of the proposed fabric-based pressure sensor, a colour-coded mesh plot was developed to visualise the sensor data. The reliability of the sensor was tested using a portable load cell. Pressure profile of the proposed multi-array fabric-based pressure sensor shows comparable profile to that of the commercialized pressure sensor. The main advantage of the proposed sensor is that it is flexible and adaptable making it suitable to be interfaced with the human body. A case study was performed on an able-bodied person and two tetraplegic patients who used the sensor as the pillow cover. Findings from this case study have demonstrated the ability to map the force on the surface of the pillow and subsequently the location of the force applied with 71% accuracy and 70% sensitivity. This feature makes it suitable to detect the pattern of head movement and hence a call bell for patients with special needs.